2015
DOI: 10.1364/ao.54.009703
|View full text |Cite
|
Sign up to set email alerts
|

Z-scan studies of the nonlinear optical properties of gold nanoparticles prepared by electron beam deposition

Abstract: This paper details the fabrication process for placing single-layer gold (Au) nanoparticles on a planar substrate, and investigation of the resulting optical properties that can be exploited for nonlinear optics applications. Preparation of Au nanoparticles on the substrate involved electron beam deposition and subsequent thermal dewetting. The obtained thin films of Au had a variation in thicknesses related to the controllable deposition time during the electron beam deposition process. These samples were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…It has been reported that nonlinear optical properties of Au-NPs by means of electron beam deposition have been studied by employing Z-scan technique [17]. It is worth highlighting that Z-scan technique is a simple and accurate technique which can be useful in determining the nonlinear (NL) properties.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that nonlinear optical properties of Au-NPs by means of electron beam deposition have been studied by employing Z-scan technique [17]. It is worth highlighting that Z-scan technique is a simple and accurate technique which can be useful in determining the nonlinear (NL) properties.…”
Section: Introductionmentioning
confidence: 99%
“…Since SPR coexists in metal nanoparticles, the OCR resulting absorption should not be confused with SPR and the resulting photon absorption. The two resonances always have different frequencies [27][28][29][30][31][32]. Only when q is near zero, these two frequencies approach the same value.…”
Section: Difference Between Ocr and Sprmentioning
confidence: 98%
“…Only at a very low concentration of metal nanoparticles, the OCR and surface plasmon resonance (SPR) occur at the same frequency [27,28]. As far as I know, the ion implantation laser ablation [29], electron beam deposition [30], and sputtering techniques are commonly used to fabricate metal nanoparticle-dielectric thin films with high volume fraction of metal nanoparticles. This work reports using the electrostatic self-assembly (ESA) technique to fabricate two-dimensional (2D) Au nanoparticle arraydielectric thin films containing high volume fraction of Au nanoparticles to investigate this type of resonance through theoretical calculations and experimental characterizations.…”
Section: Introductionmentioning
confidence: 99%
“…Наночастицы (НЧ) благородных металлов проявляют уникальные нелинейно-оптические свойства благодаря особому механизму взаимодействия с лазерным излучением, связанному с существованием коллективных электронных возбуждений, называемых в литературе локализованными или поверхностными плазмонами, время жизни которых ограничено и определяется электронэлектронной (∼ 10 2 fs) и электрон-фононной релаксацией (до 10 2 ps) [1][2][3][4][5].…”
Section: Introductionunclassified